Immobilisation of ketone catalyst: a method to prevent ketone catalyst from decomposing during dioxirane-mediated epoxidation of alkenes - Song, CE; Lim, JS; Kim, SC; Lee, KJ; Chi, DY (ROYAL SOC CHEMISTRY, 2000)
Covalent attachment of trifluoromethyl ketone catalyst to a solid support such as silica gel increased the stability of catalyst dramatically, so solving an intrinsic problem of dioxirane-mediated epoxidation of alkenes catalysed by ketones.
Keywords: CHIRAL STATIONARY PHASES; CINCHONA ALKALOIDS; SILICA; OXIDATIONS; CHEMISTRY; OXIDANTS; OLEFINS